Water coning mechanism in Tarim fractured sandstone gas reservoirs - Shen, Wei-jun; Liu, Xiao-hua; Li, Xi-zhe; Lu, Jia-liang (Journal of Central South University, 2015)
The problem of water coning into the Tarim fractured sandstone gas reservoirs becomes one of the major concerns in terms of productivity, increased operating costs and environmental effects. Water coning is a phenomenon caused by the imbalance between gravity and viscous forces around the completion interval. There are several controllable and uncontrollable parameters influencing this problem. In order to simulate the key parameters affecting the water coning phenomenon, a model was developed to represent a single well with an underlying aquifer using the fractured sandstone gas reservoir data of the A-Well in Dina gas fields. The parametric study was performed by varying six properties individually over a representative range. The results show that matrix permeability, well penetration (especially fracture permeability), vertical-to-horizontal permeability ratio, aquifer size and gas production rate have considerable effect on water coning in the fractured gas reservoirs. Thus, investigation of the effective parameters is necessary to understand the mechanism of water coning phenomenon. Simulation of the problem helps to optimize the conditions in which the breakthrough of water coning is delayed.